The long shadow of an infection: COVID-19 and performance at work - Kai Fischer; J. James Reade; W. Benedikt Schmal (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2021)
The COVID-19 pandemic has caused economic shock waves across the globe. Much research addresses direct health implications of an infection, but to date little is known about how this shapes lasting economic effects. This paper estimates the workplace productivity effects of COVID-19 by studying performance of soccer players after an infection. We construct a dataset that encompasses all traceable infections in the elite leagues of Germany and Italy. Relying on a staggered difference-in-differences design, we identify negative short- and longer-run performance effects. Relative to their preinfection outcomes, infected players' performance temporarily drops by more than 6%. Over half a year later, it is still around 5% lower. The negative effects appear to have notable spillovers on team performance. We argue that our results could have important implications for labor markets and public health in general. Countries and firms with more infections might face economic disadvantages that exceed the temporary pandemic shock due to potentially long-lasting reductions in productivity.
Keywords: I18; J24; J44; 330; Labor Performance; Economic Costs of COVID-19; Public Health